Financial Evaluation of Strawberry Cultivation in Greenhouses in Tartous Governorate - مرهج موسى; صقر إبراهيم; سلمان فؤاد (Latakia University Journal -Biological Sciences Series, 2023)
The objective of this research is to study the reality of farming and producing ferries within protected houses in Tartus Governorate In addition to conducting a descriptive economic analysis of the costs and revenues of the livestock crop within the province’s protected houses for the 2022-2021 agricultural season, Using a questionnaire form by interviewing researchers The sample included 300 strawberry farmers in areas of Tartus governorate where strawberry farming is prevalent in protected houses (Tartus Administrative District, Safita District). The results showed that ferries cultivated in protected homes accounted for about 42% of the total area cultivated, the same percentage (42%) of production, and the number of protected homes cultivated in Syria. The results also showed that the production costs of fries in protected houses in Tartus governorate were approximately. 2745831.45 S.P, gross product was approximately 3300000 S.P., which the profit achieved was approximately 554168.55 S.P, as well as the value of each gross margin, was about 1332990 S.P, while the capital recovery time was 4.95 years, productive efficiency 1.35, economic efficiency 1.20. The research concluded a series of recommendations, the most important of this working to reduce total production costs, and establishing cooperative societies for perishable agricultural products, including strawberries.